Financial Sector Assessment : Malaysia - World Bank (Washington, DC, 2013)
Malaysia, as many of its Asian neighbors, experienced significant macro/financial distress in the late 1990s. The transformed and strengthened financial sector has been able to weather the recent global financial crisis well. Financial market intermediaries reliance on cross-border and interbank funding remains limited. Banking institutions are well capitalized and are expected to be able to meet Basel three capital requirements comfortably by the 2019 implementation deadline. Asset quality has improved significantly over the last 5 years and banks are profitable, with low cost-to-income ratios compared to regional peers. The authorities have taken steps to monitor and mitigate the potential significant risks of recent rapid loan growth. The regulatory and supervisory regimes for banking, insurance and securities are well developed and exhibit a high degree of compliance with international standards. Government equity holdings in the financial sector, both direct and indirect, are extensive. Further development of the domestic Islamic financial system presents both opportunities and challenges.